PERAN STRATEGI PEMOLISIAN MASYARAKAT DALAM PENCEGAHAN EKSTREMISME KEKERASAN YANG MENGARAH PADA TERORISME - Indah Pangestu Amaritasari (Abdi Bhara, 2023)
A strategy on community-oriented policing is belivedto be the soft approach in countering violent extremism leadingto terrorism, especially when it is mandated under thePresidential Regulation No, 7 year 2021 on National Action Planon Preventing and Countering Violent Extremism. However,there are often misinterpret the strategy to be an approach toencourage civilians to do surveilence, which can create suspicionand tention between community. Thus, it is important to havesocialication, as part of academic community service, to raiseawareness of the strategy to be proper in place to relevantstakeholders, ultimately the community policing officersespecially at village level (Bhabinkamtibmas). The trainingorganized by Jakarta Law Enforcement Center (JCLEC), onwhich the author has participated to deliver the training, hasgiven significant impact especially in relation to actions made byparticipants from their new acquired knowledge. The adultlearningmethod (andragogy) applied in the training hasenchirced the participants experience and knowledge which isneeded for the skill improvement of the participants for using thestrategy properly.